2002
DOI: 10.2337/diabetes.51.6.1907
|View full text |Cite
|
Sign up to set email alerts
|

Female Rats Do Not Exhibit Free Fatty Acid–Induced Insulin Resistance

Abstract: It is well described that excessive lipid metabolism can cause insulin resistance in both animals and humans, and this has been implicated as a causative factor in the development of insulin resistance and type 2 diabetes in humans. Recently, we have shown that intravenous lipid emulsion (liposyn) infusion during a 120-min euglycemichyperinsulinemic clamp led to significant reductions in insulin action and fatty acid translocase (FAT/CD36) skeletal muscle protein expression. After reviewing the literature, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
67
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 37 publications
(35 reference statements)
12
67
0
1
Order By: Relevance
“…Some studies have reported such differences to be specific to developmental time windows (28) or to specific traits, such as plasma glucose and adiponectin levels, blood pressure, endothelial function, and visceral and subcutaneous fat deposits (1,20,22). As previously suggested for rats (10,16,19,28), female sex hormones may protect against the development of insulin resistance and associated disorders. In our experiments, the differences in adaptive programming between the two sexes apply to glucose and insulin, but not to lipids.…”
Section: Discussionmentioning
confidence: 91%
“…Some studies have reported such differences to be specific to developmental time windows (28) or to specific traits, such as plasma glucose and adiponectin levels, blood pressure, endothelial function, and visceral and subcutaneous fat deposits (1,20,22). As previously suggested for rats (10,16,19,28), female sex hormones may protect against the development of insulin resistance and associated disorders. In our experiments, the differences in adaptive programming between the two sexes apply to glucose and insulin, but not to lipids.…”
Section: Discussionmentioning
confidence: 91%
“…Consequently, male and female mice have comparable levels of Acrp30 protein in the hexamer form, but females have a vast excess of the higher order structure complex. It is an intriguing hypothesis that the sexually dimorphic absolute Acrp30 levels and differential distribution between the forms may be partly responsible for the increased insulin sensitivity of females compared with males and the reduced susceptibility of females to the deleterious actions of free fatty acids (30,31). Furthermore, it leads to the hypothesis that the hexamer is the "necessary" form of Acrp30, required for basal activity of this protein; despite the tremendous difference in absolute levels of circulating Acrp30 between the genders, male and female animals have similar levels of the hexamer.…”
Section: Acrp30(c39s) Is Secreted More Efficiently and Is Susceptiblementioning
confidence: 99%
“…Human 1,2 as well as animal studies [3][4][5][6][7] demonstrate less severe obesity-related metabolic disorders including peripheral tissue insulin resistance and dyslipidemia (i.e., the components of metabolic syndrome), and/or later onset of these adverse phenotypes in female than in male subjects. However, mechanisms underlying a relatively low susceptibility of females to metabolic syndrome remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%